AI-Supported Classroom Learning: Strengthening Students’ Creativity, Critical Thinking, Confidence, and Growth Mindset - Retno Azizah; Ummi Kulsum; Ziadatu Zzulfa; Roni Sulistiyono (Jurnal Praktik Baik Pembelajaran Sekolah dan Pesantren, 2026)
The rapid integration of artificial intelligence (AI) in educational environments has transformed teaching and learning processes worldwide. AI-based tools provide adaptive learning environments, personalized feedback, and new opportunities for reflective learning that may foster students’ growth mindset and higher-order thinking skills. This study explores how AI can influence students’ confidence, reflective learning, creativity, and critical thinking in classroom settings. Using a qualitative literature review approach, this research analyzes recent scholarly works on AI in education from the past five years. The findings indicate that AI can function as a cognitive partner that enhances students’ self-confidence, supports reflective evaluation of mistakes, stimulates creativity, and promotes critical thinking skills when integrated with appropriate pedagogical strategies. However, the impact of AI also depends heavily on instructional design and students’ AI literacy. The results suggest that educators should use AI not merely as a technological tool but as a scaffold for developing a growth mindset and deeper cognitive engagement in learning. The study proposes a framework for AI-supported classroom learning that integrates reflective practice, metacognitive feedback, and creative exploration to enhance student learning outcomes.